Some Thoughts on Legal Education - Palmer, Geoffrey (Victoria University of Wellington Law Review, 2017)
As well as holding a practicing certificate for over 50 years, Sir Geoffrey Palmer has spent years teaching law, both in the United States and in New Zealand. Here, he reflects on his experiences of the law as a student, a practitioner and as a teacher and makes some observations about what this means for the discipline of law. The address concludes with the thought that what it means to be learned in the law is changing, and legal education has to change with it. Address delivered at the Australian Law Teachers Association (ALTA) 2016 Conference in Wellington on 7 July 2016.